Goals-Related Motivation in Learning English - Siti Danti; Lala Nining Indrawa; Taufiq Kurniawan (Departement of Mathematics Education, 2023)
English is arguably the most widely used language in the world and it is considered as the mother tongue by more than 400 million people. It is underlines the impotance of mastering English and the scope of English which is too broad makes everyone has different motivations in learning English. The purpose of this research is to investigate the differences motivation in learning English as a foreign language. The participants of this study were 5 people from different backgrounds based on their needs to support them in living their lives. They were from student, lecturer, awardee of scholarship, worker, and course-taking people. This research method employed a descriptive qualitative method. The sample was taken using purposive sampling since data collection was in accordance with their respective positions. Data collection techniques included observation, interview, and documentation. The results and discussion will be further presented.